Development of Interactive E-Modules Based on N-Track Studio to Improve Students' Digital Music Writing Competence - Maulana, Muhammad Ahsin; Samosir, Hendro T.G.; Natalina, Kristiani; Situmorang, Hidaka Hita; Aghisna, Aghisna (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The transformation of music education in the digital age requires the integration of music theory and mastery of digital music writing technology. This study aims to develop an interactive e-module based on N-Track Studio as a learning medium for the Computer Music Writing course in the Performing Arts Education Study Program at the University of Palangka Raya. The method used is Research and Development (R&D) with the ADDIE model, which includes the stages of needs analysis, design, product development, implementation, and evaluation. The validation results by subject matter experts, language experts, and media experts obtained an average score of 83.3%, which was categorized as sufficiently valid. Field trials with 20 students showed an excellent response with an average score of 90%, in terms of ease of use, appearance, and learning effectiveness. The research results indicate that the N-Track Studio-based e-module is capable of improving students' understanding of digital music concepts and DAW-based music writing skills. Thus, this e-module is suitable for use as a learning medium and can be further developed in the context of other digital music learning.